The woman's hour : our fight for the right to vote : adapted for young readers - Weiss, Elaine F., 1952- (Random House, 2020)
Presents information about the suffragist movement in the United States during the twentieth century and the final campaign to get equal rights for women including the right to vote. Profiles many of the women who were pivotal leaders in the suffragist movement, and details how Nashville, Tennessee, became a battleground for the movement. Includes black-and-white photographs, fact boxes, and additional resources.